From International to Global Development: New Geographies of 21st Century Development. Issue 2 (8th December 2017) - Horner, Rory; Hulme, David
ABSTRACT: Recent claims of 21 st century global convergence and the 'rise of the South' suggest a profound and ongoing redrawing of the global map of development and inequality. This article synthesizes shifting geographies of development across economic, social and environmental dimensions, and considers their implications for the 'where' of development. Some convergence in aggregate development indicators for the global North and South during this century challenge, now more than ever, the North–South binary underlying international development. Yet convergence claims do not adequately capture change in a world where development inequalities are profound. Between‐country inequalities remain vast, while within‐country inequalities are growing in many cases. Particular attention is given here to exploring the implications of such shifting geographies, and what those mean for the spatial nomenclature and reference of development. This article concludes by arguing for the need, now more than ever, to go beyond international development considered as rich North/poor South, and to move towards a more holistic global development — where the global South remains a key, although not exclusive, focus.